Development and Validation of Highly Sensitive Spectrophotometric Methods for Cefpirome Determination in Pharmaceutical Dosage Forms - Hiremath, Basavaraj (Asian Journal of Chemistry, 2021)
Quantitative spectrophotometric determination of cefpirome in pure and pharmaceutical dosage has been developed. Method I produces a pink-coloured chromogen peak at λmax 510 nm by reacting diazotized cefpirome drugs with diphenylamine (DPA) in a neutral medium. Method II obtained of a coloured Schiff bases when cefpirome reacts with alcoholic p-dimethylaminobenzaldehyde (PDAB) to produce a yellow-coloured chromogen with a maximum absorption wavelength of 415 nm. In both methods I and II, Beer’s law is followed in the concentration ranges of 0.3-3.0 and 0.5-5.0 μg/mL, respectively, with molar absorptivity of 5.13 × 104 and 2.54 × 104 for each form. At three separate concentrations, intra-day and inter-day (RSD) and relative error (RE) are measured. The current methods are simple, reliable, inexpensive, speedy and highly reproducible and have been tested in broad range of pharmaceutical formulations with statistical comparisons to reference methods.